Tinjauan Literatur Tentang Faktor-Faktor yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Pekerja Konstruksi - Niswatun Najihah; Andriyani Andriyani; Ayunda Larasati Sekarputri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to identify and analyze the factors influencing compliance with the use of Personal Protective Equipment (PPE) among construction workers through a literature review. Despite its importance, non-compliance with PPE usage remains a persistent issue. This research utilized a qualitative descriptive method and was conducted from January to April 2025. A total of 15 relevant articles published between 2020 and 2025 were reviewed. These articles were obtained from various reputable national and international databases, including Google Scholar, PubMed, and ScienceDirect. The analysis revealed two primary categories of factors affecting PPE compliance: internal and external. Among these, knowledge and attitude were found to be the most dominant contributors to PPE compliance. These findings suggest that improving PPE usage among construction workers requires a multifaceted approach. Recommended strategies include strengthening workers’ knowledge through continuous education, conducting regular safety training, ensuring the availability and ergonomic design of PPE, and fostering a safety-oriented workplace culture supported by active supervision and peer encouragement. The study contributes to the understanding of behavioral on PPE use and provides insight.